2017
DOI: 10.1002/art.40042
|View full text |Cite
|
Sign up to set email alerts
|

A Dual Role of Upper Zone of Growth Plate and Cartilage Matrix–Associated Protein in Human and Mouse Osteoarthritic Cartilage: Inhibition of Aggrecanases and Promotion of Bone Turnover

Abstract: UCMA appears to link cartilage with bone changes in osteoarthritis by supporting cartilage integrity as an endogenous inhibitor of aggrecanases while also promoting osteoclastogenesis and subchondral bone turnover. Thus, UCMA represents an important link between cartilage and bone in osteoarthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
30
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 43 publications
5
30
0
Order By: Relevance
“…In parallel, Seuffert et al suggested that UCMA can inhibit the aggrecanase activity of A Disintegrin and Metalloproteinase with Thrombospondin motifs 5 via binding and provides protection against cartilage degeneration . In addition, it was shown that UCMA deficiency resulted in reduced osteophyte formation and subchondral sclerosis . These results are in line with our findings and suggest that cartilage matrix can exert chondroprotective effects by augmenting UCMA synthesis against proteolytic deterioration in knee OA patients.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In parallel, Seuffert et al suggested that UCMA can inhibit the aggrecanase activity of A Disintegrin and Metalloproteinase with Thrombospondin motifs 5 via binding and provides protection against cartilage degeneration . In addition, it was shown that UCMA deficiency resulted in reduced osteophyte formation and subchondral sclerosis . These results are in line with our findings and suggest that cartilage matrix can exert chondroprotective effects by augmenting UCMA synthesis against proteolytic deterioration in knee OA patients.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, Stock et al demonstrated in vivo that UCMA was highly expressed in human and mouse cartilage tissues compared to control groups . These results are remarkable on the basis of underlying protective effects of UCMA in cartilage tissue during the course of OA.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations